Perlindungan Hukum Masyarakat Adat di Wilayah Pertambangan (Lex Jurnalica, 2013)
AbstractThe operations of the mining region of indigenous people in recent decades caused quite a variety of issues considered to adversely affect the interests of indigenous people, so interesting to study more about the legal protection of indigenous peoples in the management of mining and the role of State to provide protection and welfare of indigenous peoples in mining areas. The research specification is analytical descriptive with normative juridic approach. Data analytical and conclusion of the research use qualitative method and will be presented in analytical descriptive. The rights of indigenous peoples have the constitutional basis and a solid legal basis, the provisions of Article 18B paragraph (2) Constitution in 1945, which regulates that: "The State recognizes and respects the public entities customary law and traditional rights over still alive and in accordance with the development of society and the principles of the Unitary Republic of Indonesia, which stipulated in the Act ". Government especially the local government has a role and responsibility to supervise the management of the mine in the territories of indigenous peoples, in order to follow the provisions of the mining concession has been established, as well as ensuring the safety and welfare of the surrounding community.Keywords: protection, indigenous peoples, the mining region AbstrakKegiatan usaha pertambangan diwilayah masyarakat adat dalam beberapa dekade ini cukup menimbulkan berbagai permasalahan yang dinilai banyak merugikan kepentingan mereka, sehingga menarik untuk diteliti lebih lanjut mengenai perlindungan hukum masyarakat adat dalam pengelolaan pertambangan, serta peranan Negara/Pemerintah dalam memberikan perlindungan dan peningkatan kesejahteraan masyarakat adat  di wilayah pertambangan. Artikel ini merupakan hasil penelitian dengan menggunakan pendekatan Yuridis-Normatif dan bersifat Deskriptif Analitis, yang menggambarkan dan menganalisis ketentuan-ketentuan yang ada dalam peraturan perundang-undangan. Pengakuan hak-hak adat  memiliki landasan konstitusional yang kuat sebagaimana tercantum dalam Pasal 18B ayat (2) UUD1945 bahwa  Negara mengakui dan menghormati kesatuan-kesatuan masyarakat hukum adat beserta hak- hak tradisionalnya sepanjang masih hidup dan sesuai dengan perkembangan masyarakat dan prinsip-prinsip Negara Kesatuan Republik Indonesia yang diatur dalam Undang-Undang. Pemerintah khususnya Pemda memiliki peranan dan tanggung jawab untuk melakukan pengawasan pengelolaan tambang di wilayah masyarakat adat, agar pengusahaan tambang mengikuti ketentuan yang telah ditetapkan, serta menjamin keselamatan dan kesejahteraan masyarakat sekitarnya.Kata kunci: perlindungan, masyarakat adat, wilayah pertambangan